(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Optic Neuritis And Papilledema Are Important Causes Of Optic Nerve Dysfunction And Visual Impairment. Structural Changes In The Retinal Nerve Fibre Layer (Rnfl) And Ganglion Cell Layer (Gcl) Can Be Objectively Assessed Using Spectral Domain Optical Coherence Tomography (Sd-Oct), Which Provides Valuable Information Regarding Axonal And Neuronal Damage. This Study Was Undertaken To Evaluate Rnfl And Gcl Thickness In Patients With Optic Neuritis And Papilloedema Using Sd-Oct. Methodology: This Hospital-Based Observational Study Was Conducted In The Department Of Ophthalmology, Sree Mookambika Institute Of Medical Sciences, Kulasekharam, From February 2025 To October 2025. Patients Aged 18–65 Years Diagnosed With Optic Neuritis Or Papilloedema Were Included. Detailed Clinical Evaluation, Visual Acuity Assessment, Fundus Examination, And Sd-Oct Imaging Were Performed. Rnfl And Gcl Thickness Measurements Were Obtained Using Zeiss Cirrus 500 Oct And Compared With Fellow Eyes Or Age-Matched Healthy Controls. Statistical Analysis Was Performed Using Spss Version 25.0, With P<0.05 Considered Statistically Significant. Results: Patients With Acute Optic Neuritis Demonstrated Increased Rnfl Thickness Due To Optic Nerve Edema, Whereas Chronic Cases Showed Significant Rnfl Thinning Associated With Axonal Loss. In Papilloedema, Average Rnfl Thickness Was Significantly Increased Compared To Controls, Reflecting Optic Disc Edema Secondary To Raised Intracranial Pressure. Significant Thinning Of The Ganglion Cell Layer Was Observed In Both Optic Neuritis And Papilloedema Groups, Indicating Retinal Ganglion Cell Damage. Sd-Oct Effectively Detected And Quantified These Structural Alterations, Facilitating Objective Assessment Of Disease Severity. Conclusion: Sd-Oct Is A Valuable Non-Invasive Tool For Evaluating Structural Retinal Changes In Optic Neuritis And Papilloedema. Combined Assessment Of Rnfl And Gcl Thickness Provides Important Information Regarding Axonal And Neuronal Integrity, Aiding Diagnosis, Monitoring Disease Progression, And Predicting Visual Outcomes.